Dendriform pulmonary ossification in a patient with mucoepidermoid carcinoma. (July 2016) - Triki, Meriam; Kallel, Rim; Hentati, Abdessalem; Hentati, Yosr; Mnif, Hela; Boudawara, Tahya
Dendriform pulmonary ossification is a chronic process characterized by the presence of heterotopic bone within the interstitium and alveolar walls. It usually occurs in the setting of chronic inflammation. We report an unusual case of a 54-year-old man with a history of relapsing Hodgkin lymphoma who was diagnosed with concomitant mucoepidermoid pulmonary carcinoma and dendriform ossifications. The radiological features were initially misinterpreted as post-radiation pulmonary fibrosis and bronchiectasis. The diagnosis was finally established after considering both the radiological and pathological findings. Dendriform pulmonary ossification is an under-recognized disease that should be considered in the differential diagnosis of lung chronic diseases.